Best Practice Penerapan Model Pembelajaran Presentasi Pada Proses Perkuliahan Mahasiswa Pendidikan Agama Islam - Rohana, Sy.; Suharman, Suharman; Maulana, Heru (Hikmah, 2024)
In the lecture process, learning models are very important to support good lecture quality. One of the models that can be used is the presentation model. The presentation model involves the presentation of lecture material by students in front of their peers or in front of the class, either individually or in groups, with material that has been determined by the lecturer. The purpose of this study was to evaluate the effectiveness of the presentation model in improving students' responsibility, objectivity, problem identification ability, active participation, and communication skills. This research uses a qualitative method, using a narrative study approach, which describes narratively the learning practices with the presentation model that have been implemented. Data were collected through observation, interview and documentation study. The research informants were lecturers and students. The results showed that the presentation model is very effective in the lecture process. In addition to increasing effectiveness, this model can also increase student creativity and motivation to learn. However, the drawback is the need for facilities and infrastructure as well as careful preparation. This research has implications for the best presentation learning model, which can be used by other lecturers, either at the same institution or at other institutions.